Function and significance of MicroRNAs in benign and malignant human stem cells. (December 2015) - Utikal, Jochen; Abba, Mohammed; Novak, Daniel; Moniuszko, Marcin; Allgayer, Heike
Abstract: MicroRNAs now not only represent a significant mechanism for post-transcriptional gene regulation, but have come to be appreciated as molecules with far reaching tentacles affecting diverse processes and pathologies by modulating amongst others, cellular gene expression, epigentic mechanisms, complex signaling cascades, cell–cell communication, the immune system and microenvironmental interactions between several cell types, tissues and organ systems. In this review, we systematically reflect on the impact of miRNAs on all types of benign and malignant human stem cells, looking at the roles they play in maintaining or changing the stem cell state, and review how aberrations of their expression and function within diverse types of stem cells orchestrate carcinogenesis and metastasis. As a conclusion, we consider it striking to see how similar some miR-driven mechanisms are between different types of stem cells and cancer cells, and how this might support hypotheses of miR-driven embryologic pathway reactivation in metastasis or propose putative functions of miRs in important novel cross-topic fields such as obesity and cancer.